A study to evaluate the introduction of the Newborn Infant Physical Examination knowledge and skills into an undergraduate pre-registration midwifery education programme. (March 2021) - Way, Susan; Cescutti-Butler, Luisa; Irving, Michelle
Abstract: Newborn Infant Physical Examination is recommended between six to 72 h from birth and the midwife is ideally placed to undertake this screening examination. In the United Kingdom only a small percentage of midwives are competent to undertake this screening, and is usually taught once qualified. The aim of this qualitative study was to explore the experiences of student midwives in relation to the impact and effectiveness of introducing the theory of Newborn Infant Physical Examination into an undergraduate midwifery curriculum and the opportunity to apply the skills in practice. Two focus groups with final year student midwives (n = 11) were undertaken. The transcribed interviews were reviewed by the researchers and thematically analysed. Three themes emerged: i) timing of the theoretical content, ii) applying theory to practice iii) holistic care. Recommendations include the importance of incorporating the theoretical elements into the programme even if students do not have the opportunity to become competent in the required skills. Most students favoured the theory elements to be threaded throughout the three year programme rather than having a single dedicated module. Students identified that when midwives completed the newborn examination, holistic care was improved.